1993
DOI: 10.1007/bf00114977
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption suppresses metastasis of B16-BL6 melanoma in mice

Abstract: Female C57BL/6 mice were fed a defined, pelleted diet and given 10% w/v or 20% w/v ethanol in their drinking water. Natural killer (NK) cell cytolytic activity was compared between water-drinking and ethanol-consuming mice and in mice that were also treated with polyinosinic-polycytidylic acid (poly I:C) to augment NK cell activity or with anti-NK1.1 antibody to decrease activity. NK cell cytolytic activity was not altered in mice given 10% ethanol, but was decreased in mice given 20% ethanol compared to water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 27 publications
0
16
1
Order By: Relevance
“…It is unknown whether abnormal diurnal PC variation is associated with suppressed NK cell activity. Splenic NK cell cytolytic activity is not suppressed in mice fed 10% w/v ethanol for 4 weeks (29). This concentration of ethanol lies between those (7.5-20% w/v) that induce dampening of PC periodicity.…”
Section: Discussionmentioning
confidence: 88%
“…It is unknown whether abnormal diurnal PC variation is associated with suppressed NK cell activity. Splenic NK cell cytolytic activity is not suppressed in mice fed 10% w/v ethanol for 4 weeks (29). This concentration of ethanol lies between those (7.5-20% w/v) that induce dampening of PC periodicity.…”
Section: Discussionmentioning
confidence: 88%
“…25,26 Yirmiya et al 10 and Ben-Eliyahu et al 11 showed that ethanol intake promotes tumor metastasis by suppressing natural killer cell activity in the rat. In contrast, Meadows et al 12 speculated that alcohol consumption suppresses metastasis rather than suppressing natural killer cell activity in mice.…”
Section: Discussionmentioning
confidence: 93%
“…Two recent reports demonstrated that alcohol consumption did not signifi cantly affect the metastasis of duodenal wall gastrinomas and laryngeal squamous cell cancers, which are two types of cancer that are related to alcohol consumption [ 40 , 41 ]. Using the mouse chronic alcohol consumption and B16BL6 melanoma model, we found that alcohol consumption inhibited B16BL6 lung metastasis [ 26 ]. This inhibition is independent of perforin and granzyme-induced NK cell cytotoxic effects [ 42 ].…”
Section: Chronic Alcohol Consumption Inhibits B16bl6 Melanoma Lung Mementioning
confidence: 97%
“…A paradoxical observation is that while alcohol consumption is associated with a decrease in the incidence of Non-Hodgkin's Lymphoma (NHL) [ 20 -22 ], it also decreases the survival of these patients [ 23 -25 ]. In our mouse studies, chronic alcohol consumption inhibits lung metastasis of B16BL6 melanoma inoculated intravenously [ 26 ]; however, survival of mice bearing subcutaneous melanomas is decreased [ 27 ].…”
Section: Introductionmentioning
confidence: 97%